Semantic interoperability for asset communication within smart factories - Diedrich, Christian; Belyaev, Alexander; Schroder, Tizian; Vialkowitsch, Jens; Willmann, Alexander; Uslander, Thomas; Koziolek, Heiko; Wende, Jorg; Pethig, Florian; Niggemann, Oliver (2017 22nd IEEE International Conference on Emerging Technologies and Factory Automation (ETFA), 2017)
Industrie 4.0 (I4.0) aims at a manufacturer-independent, vertical- and horizontal-oriented communication and cooperation within smart factories. This is only manageable using international standards. The so-called reference architecture model for Industrie 4.0 (RAMI4.0) and the requirement specification of an I4.0 component are already available. RAMI4.0 could be the basis for the interoperability of the interactions. The working group "Semantic and interaction model for I4.0 components" (GMA 7.20) made progress in this direction. The language used for the interaction of I4.0 components needs model definitions for the interaction consisting of the structure of the components, syntax for the description of the messages and the means to assign the meaning to the language elements. This paper discusses the results for a broader audience.